Mesenchymal Stem Cells and Tuberculosis: Clinical Challenges and Opportunities - Zhang, Xueying; Xie, Qi; Ye, Ziyu; Li, Yanyun; Che, Zhengping; Huang, Mingyuan; Zeng, Jincheng (Frontiers in Immunology, 2021)
Tuberculosis (TB) is one of the communicable diseases caused by Mycobacterium tuberculosis (Mtb) infection, affecting nearly one-third of the world’s population. However, because the pathogenesis of TB is still not fully understood and the development of anti-TB drug is slow, TB remains a global public health problem. In recent years, with the gradual discovery and confirmation of the immunomodulatory properties of mesenchymal stem cells (MSCs), more and more studies, including our team’s research, have shown that MSCs seem to be closely related to the growth status of Mtb and the occurrence and development of TB, which is expected to bring new hope for the clinical treatment of TB. This article reviews the relationship between MSCs and the occurrence and development of TB and the potential application of MSCs in the treatment of TB.